THE INTERSECTION OF ISLAMIC LAW AND MODERN HUMAN RIGHTS - Dr Syed Maisoor Hussain (Journal of Religion and Society, 2025)
The intersection of Islamic law and modern human rights is a complex and evolving field of study, characterized by the interplay of religious traditions and international legal frameworks. Islamic law, or Sharia, has historically governed many aspects of life in Muslim-majority societies, addressing issues ranging from family and social relations to criminal justice. However, with the rise of modern human rights concepts, particularly in the post-World War II era, a tension has emerged between traditional Islamic legal principles and contemporary notions of individual rights, freedom, and equality. This paper explores the ways in which Islamic law and modern human rights intersect, considering both the areas of congruence and divergence. On one hand, certain aspects of Islamic law align with modern human rights principles, such as the protection of life, property, and the right to justice. Islamic legal texts emphasize the dignity and equality of all human beings, and many scholars argue that these principles provide a basis for human rights in the Islamic tradition. On the other hand, challenges arise in areas such as gender equality, freedom of expression, and religious freedom, where Islamic legal interpretations often conflict with international human rights standards.This paper examines the historical and doctrinal foundations of both Islamic law and modern human rights, analyzing their potential for coexistence. It also explores the role of Islamic scholars, policymakers, and human rights advocates in seeking a balance between these two systems. By critically assessing the potential for reform within Islamic legal frameworks and the adaptability of international human rights law to diverse cultural contexts, the paper provides a nuanced perspective on how Islamic law can evolve in alignment with modern human rights principles while respecting its theological roots. Keywords: Islamic law, Sharia, modern human rights, gender equality, freedom of expression, international law, religious freedom, legal reform, human dignity, cultural adaptation.